A novel mutation in PSEN1 (p.Arg41Ser) in an Argentinian woman with early onset Parkinsonism. (August 2020) - Gatto, Emilia M.; Rojas, Galeno J.; Nemirovsky, Sergio I.; Da Prat, Gustavo; Persi, Gabriel; Cesarini, Martin; Etcheverry, Jose L.; Rojas, Natalia Gonzalez; Parisi, Virginia; Cordoba, Marta; Sevlever, Gustavo; Allegri, Ricardo F.; et al.
Abstract: Introduction: Mutations in presenilin-1 (PSEN1) account for the majority of cases of familial autosomal dominant early-onset Alzheimer's disease (AD) as well as in sporadic forms. Atypical presentations are reported including extrapyramidal signs. In the last years, a pleiotropic effect of some PSEN1 variants has been reported in Parkinson's disease (PD). Objective: to report a new PSEN1 mutation characterized by early-onset Parkinsonism (EOPD) without dementia or classical AD biomarkers phenotype. Patient and methods: An Argentinian 46 years old woman was diagnosed with EOPD at 35 years old with no family history of neurodegenerative disorders. Her medical history included iron deficiency and anemia since childhood. A brain MRI showed moderate frontal atrophy. 18 FDG-PET and PiB-PET as well as CSF biomarkers were inconclusive for AD. Two neuropsychological examinations were compatible with a mild non amnestic cognitive impairment. Whole blood DNA was extracted and whole exome sequencing and analysis was performed. Results and conclusion: A heterozygous novel missense PSEN1 mutation (position 14:73637540, A > T, pArg41Ser) was identified as a likely causative mutation in this patient. To the best of our knowledge, this case is the first PSEN1 mutation with a l -dopa responsive Parkinsonism lacking distinctive classical AD biomarkers. This case opens a new window to explore the pathophysiological link among PSEN1 and EOPDs and contributes to increase the phenotypes of PSEN1 variants. Highlights: PSEN1 mutations account for the majority of cases of familial early-onset Alzheimer's disease (AD). Atypical phenotype have been reported including extrapyramidal signs. A pleiotropic effect of some PSEN1 variants has been reported in Parkinson's disease (PD). A PSEN1 mutation appears as a causative mutation of early onset parkinsonism lacking AD biomarkers.